Communication research measures III a sourcebook - Graham, Elizabeth E.Graham, Elizabeth E. (Routledge communication series, 2020)
Building on the measures included in the original 1994 volume and subsequent 2009 volume, Communication Research Measures III: A Sourcebook extends its coverage of measurement issues and trends across the entire communication discipline. Volume III features entirely new content and offers an assessment of new measures in mass, interpersonal, instructional, group, organizational, family, health, and intercultural communication and highlights work in emergent subdisciplines in communication, including social media and new communication technologies, sports communication, and public relations. The "best of the best" from 2009 through today, the profiled research measures in Volume III serve as models for future scale development and constitute the main tools that researchers can use for self-administered measurement of people's attitudes, conceptions of themselves, and perceptions of others. This book is ideal for undergraduate and graduate courses that emphasize quantitative research methods, measurement, and/or survey design across communication studies disciplines"--